Imaging of equine septic discospondylitis using MRI, CT and post‐mortem radiographs. (25th January 2022) - Geller, Morgan; Slater, Robert; Graham‐Williams, Elizabeth; Wolf, Tatiana; Spriet, Mathieu; Berryhill, Emily; Skipper, Lauren; Aleman, Monica
Summary: This report describes a case of septic discospondylitis in an 11‐year‐old American Miniature stallion. Key imaging features are described here and include Fast Spin Echo T2/STIR hyperintensity on MRI of the intervertebral disc space and surrounding soft tissues as well as vertebral endplate destruction. Spinal cord deformation was seen concurrently and is considered likely secondary to either associated inflammatory granulation tissue or disc herniation. These findings most likely explain the apparent cervical pain and spinal ataxia grade 2/5 due to cervical spinal cord disease in this case.